2021
DOI: 10.4049/immunohorizons.2100055
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Healthy and Atopic Dermatitis Samples Reveals the Role of IL-37 in Human Skin

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease that affects up to one in five children and millions of adults in developed countries. Clinically, AD skin lesions manifest as subacute and/or chronic lichenified eczematous plaques, which are often intensely pruritic and prone to secondary bacterial and viral infections. Despite the emergence of novel therapeutic agents, treatment options and outcomes for AD remain suboptimal. An improved understanding of AD pathogenesis may help improve patient ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…47 It has been suggested that IL-37 plays a role in keeping an intact skin barrier and that Th2 cytokines down-regulate IL-37 expression. 48 In accordance, we found strongly down-regulated IL37 levels associated with high levels of Th2 cytokines in individuals with severe allergy. In a previous study, we found strongly downregulated skin barrier proteins in the same individuals with severe allergy to PPD.…”
Section: Discussionsupporting
confidence: 82%
“…47 It has been suggested that IL-37 plays a role in keeping an intact skin barrier and that Th2 cytokines down-regulate IL-37 expression. 48 In accordance, we found strongly down-regulated IL37 levels associated with high levels of Th2 cytokines in individuals with severe allergy. In a previous study, we found strongly downregulated skin barrier proteins in the same individuals with severe allergy to PPD.…”
Section: Discussionsupporting
confidence: 82%
“…The processing and incorporation of ceramides, fatty This systemic review found studies involving cytokines IL-4, IL-13, IL-31, IL-17, IL-31, IFN-γ, TNF-α, and GM-CSF for their effects on epidermal lipids in AD skin. In addition, it highlights the lack of studies investigating the effect on epidermal lipids of additional cytokines dysregulated in AD, such as TSLP, IL-22, IL-25, IL-33, IL-9, and IL-37 [25,49]. Most of the studies focused on cytokine analysis in AD skin have employed bulk or single-cell RNA sequencing, tissue-level proteomics, immunohistochemistry, ELISA, and Western blotting and have utilized skin biopsies or tape strips.…”
Section: Discussionmentioning
confidence: 99%
“…T H 2 cells are mainly responsible for the secretion of IL-4, IL-5, IL-13, and IL-31 cytokines in AD [5]. It is clear that the combination of T H 2 cytokines IL-4, IL-13, and IL-31, when present in the skin, induces inflammation and AD-like phenotype [48,49]. Experiments on full-thickness human skin equivalents to determine whether skin inflammation affects epidermal lipid biosynthesis showed that treatment with a cocktail of IL-4, IL-13, and IL-31 resulted in significantly lower mRNA levels of genes encoding ELOVL1, acid SMase and β-GCase, which are involved in lipid chain elongation and ceramide synthesis, suggesting a direct role of T H 2 cytokines on lipid biosynthesis and alterations in AD [33].…”
Section: Role Of T H 2-associated Cytokines In Epidermal Lipid Abnorm...mentioning
confidence: 99%
“…The functional role of the IL-18 subfamily member, IL-37 in the context of dermal inflammation remains relatively ill-defined. Several recent studies have demonstrated that IL-37 expression is decreased in lesional skin from psoriasis, AD, and Hidradenitis suppurativa (HS) patients [164][165][166] suggesting that loss of its immunosuppressive activity may be important. In addition, several studies have suggested that IL-37 may play an important role in regulating the expression of epidermal differentiation complex proteins and in maintaining a healthy skin barrier [165,167].…”
Section: Il-18 Subfamily and The Skin Microbiomementioning
confidence: 99%
“…Several recent studies have demonstrated that IL-37 expression is decreased in lesional skin from psoriasis, AD, and Hidradenitis suppurativa (HS) patients [164][165][166] suggesting that loss of its immunosuppressive activity may be important. In addition, several studies have suggested that IL-37 may play an important role in regulating the expression of epidermal differentiation complex proteins and in maintaining a healthy skin barrier [165,167]. In contrast, it has also been suggested that specific proteolytic processing leads to the expression of a proinflammatory form of IL-37 which can elicit psoriatic-like inflammatory responses in the skin, at least in part through engaging the IL-36R.…”
Section: Il-18 Subfamily and The Skin Microbiomementioning
confidence: 99%